University teachers and students’ perceptions of ELT methodologies and their effectiveness - Kim, Hughes Wilhelm; Betty Chen Pei (Penerbit UKM, 2008)
Since the mid 1970’s, a number of Asian countries have been concerned with economic reform and a firmer position in the global market. As such, a great deal of attention has been devoted to the improvement of English language teaching and learning, especially at the tertiary level. The purpose of this study was to investigate English language teaching and learning at three universities located on China’s mainland so as to identify issues worthy of more in-depth investigation. Perceptions sought from 25 English teachers and 312 English majors included: degree of satisfaction with materials and facilities; importance of English skill areas; effectiveness of teaching methods used; and factors contributing to effective language learning. Questionnaire data also included teacher/student talk time and how classes were typically structured. In addition, teachers were asked to give their views of their roles in the class and the importance of various assessment factors. Students were asked to indicate their perceptions for learning English, their perceived responsibilities in class, and their mastery of various English skills. One issue which emerged was the perception by students that they have little opportunity to practise English in the class. Teachers dominate “talk time” and this, combined with a lack of group work, indicate that little actual change has taken place regarding traditional teacher and learner roles in the classroom. Both groups were dissatisfied with textbooks and felt a lack of involvement when selecting materials or deciding syllabi. An interesting finding was the emphasis students placed on the importance of the social university environment for their success in English.